2005
DOI: 10.1556/acr.6.2005.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Implicitation in Translation: Empirical evidence for operational asymmetry in translation

Abstract: This study focuses on the notions of explicitation and implicitation in translation and aims to provide empirical evidence for operational asymmetry (Klaudy 2001). Bi-directional (SL=L1→TL=L2 and SL=L2→TL=L1) comparisons show that when explicitation takes place in the L1→L2 direction, implicitation can be observed in the L2→L1 direction. This phenomenon is referred to as symmetric explicitation. It may also happen, however, that when explicitation is carried out in the L1→L2 direction, no implicitation occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 3 publications
1
64
0
10
Order By: Relevance
“…This would make it possible to check whether generalizations in one direction are counterbalanced or not by specifications in the inverse linguistic combination (cf. the asymmetry hypothesis proposed by Klaudy & Károly 2005;Klaudy 2009). Furthermore, regarding the translation of culinary cultural referents, a comparison of the frequency of techniques used in translations from Spanish and Catalan into English would be interesting.…”
Section: Discussionmentioning
confidence: 86%
“…This would make it possible to check whether generalizations in one direction are counterbalanced or not by specifications in the inverse linguistic combination (cf. the asymmetry hypothesis proposed by Klaudy & Károly 2005;Klaudy 2009). Furthermore, regarding the translation of culinary cultural referents, a comparison of the frequency of techniques used in translations from Spanish and Catalan into English would be interesting.…”
Section: Discussionmentioning
confidence: 86%
“…In the case of normalization and levelling out, Cappelle (2012) has shown that these two reasonable-sounding candidates for universality in translation behaviour make contradictory predictions in the case of phrasal verbs. For another example, apart from the tendency of explicitation, translated language has also been claimed to display implicitation (Klaudy and Károly 2005).…”
Section: Appendix A: Prefixed Verb Contexts In Le Petit Prince With Pmentioning
confidence: 99%
“…This hypothesis has been further explored by i.a. Klaudy and Károly (2005) and Pápai (2004). Explicitation has also been considered in the context of the strategies used by both non-professional and professional translators (Laviosa-Braithwaite 1996;Puurtinen 2003;Dimitrova 2005a and b).…”
Section: Introductionmentioning
confidence: 99%